Hiking Backpack Design Development with Integrated Splint Feature for Fracture Injuries - Lunsa, Gregorius; Winta Adhitia, Guspara; Pandapotan, Daniel (Universitas Dinamika, 2024)
The background of this design is the risk of fracture injury to climbers when mountaineering. According to the International Alpine Trauma Registry (IATR), there were 306 mountaineering accidents resulting in fractures in 2019. First aid for fractures requires standardized equipment and methods to assist the rescue process. The problem studied is the difficulty of climbers in utilizing climbing equipment as splints when treating fracture victims on the mountain. The purpose of this design is to develop climbing equipment so that it can be converted into a means of bandaging to perform first aid for fracture injuries. The design method used is Quality Function Deployment (QFD), to determine the priority aspects related to the specifications of the means of massaging that users want. The result of the design is a backpack product with an internal frame that applies a collapsible mechanism so that it can be quickly accessed in an emergency and can be adjusted according to the dimensions of the body part that has a fracture injury. The developed splint design successfully meets the criteria for dimensional customization to the user's body and can immobilize the fracture according to standard first aid procedures.